"Resonant leadership: renewing yourself and connecting with others through mindfulness, hope and compassion/ by richard Boyatzis and Annie Mckee" - Boyatzis, Richard; Mckee, Annie (Boston, 2005)
The blockbuster best seller Primal Leadership introduced us to "resonant" leaders individuals who manage their own and others' emotions in ways that drive success. Leaders everywhere recognized the validity of resonant leadership, but struggled with how to achieve and sustain resonance amid the relentless demands of work and life. Now, Richard Boyatzis and Annie McKee provide an indispensable guide to overcoming the vicious cycle of stress, sacrifice, and dissonance that afflicts many leaders. Drawing from extensive multidisciplinary research and real-life stories, Resonant Leadership offers a field-tested framework for creating the resonance that fuels great leadership. Rather than constantly sacrificing themselves to workplace demands, leaders can manage the cycle using specific techniques to combat stress, avoid burnout, and renew themselves physically, mentally, and emotionally. The book reveals that the path to resonance is through mindfulness, hope, and compassion and shows how intentionally employing these qualities creates effective and enduring leadership. Great leaders are resonant leaders. Resonant Leadership offers the inspiration and tools to spark and sustain resonance in ourselves and in those we lead.
Keywords: Leadership